2004
DOI: 10.3200/genp.131.1.36-52
|View full text |Cite
|
Sign up to set email alerts
|

Body Asymmetry Affects Conjugate Lateral Eye Movement

Abstract: A. H. Baker (1989) and A. H. Baker and A. I. Ledner (1990) reported that asymmetrical visual stimulation affects conjugate lateral eye movement (CLEM). In the present article, the authors explored whether asymmetrical body position similarly affects CLEM. The authors assessed CLEMs twice in a counterbalanced design. In the control (symmetric) condition, each participant sat in a completely symmetrical position facing a wall devoid of any asymmetrical features. In the experimental (asymmetrical) condition, half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In Experiment 1 and all subsequent experiments, we seated each participant so that the head and body faced in precisely the same direction. Recent researchers have indicated that asymmetrical body orientation can influence the direction of attention and eye movements (e.g., Baker & Ledner, 2004;Grubb & Reed, 2002). Storm & Hernandez 419 420…”
Section: Methodsmentioning
confidence: 99%
“…In Experiment 1 and all subsequent experiments, we seated each participant so that the head and body faced in precisely the same direction. Recent researchers have indicated that asymmetrical body orientation can influence the direction of attention and eye movements (e.g., Baker & Ledner, 2004;Grubb & Reed, 2002). Storm & Hernandez 419 420…”
Section: Methodsmentioning
confidence: 99%